Burden and trends of ovarian and uterine cancer due to high body mass index from 1990 to 2021: an age–period–cohort study based on the GBD 2021, and projections through 2036 - Yin, Bo; Zhou, Huijuan (Frontiers in Oncology, 2025)
BackgroundOvarian cancer (OC) and uterine cancer (UC) are significant public health concerns among women of reproductive age. High body mass index (BMI) contributes to the increasing burden of these cancers globally, but comprehensive epidemiological assessments remain limited.MethodsData were obtained from the Global Burden of Disease (GBD) Study 2021 (1990–2021). Deaths, disability-adjusted life-years (DALYs), and corresponding age-standardized rates (ASRs) were calculated to assess disease burden. Burden by age was analyzed in five-year intervals. Differences across Sociodemographic Index (SDI) quintiles were compared. Temporal trends from 1990 to 2021 were assessed using estimated annual percentage change and absolute number changes. Future ASRs were projected to 2036 using a Bayesian age–period–cohort model.ResultsIn 2021, an estimated 2,022 (95% uncertainty interval [UI], 473–3,611) deaths and 99,915 (95% UI, 22,387–178,579) DALYs from OC attributable to high BMI occurred among women of reproductive age, with Eastern Europe exhibiting the highest age-standardized mortality rate and DALYs among 21 GBD regions. For UC, there were 2,202 (95% UI, 1,545–2,910) deaths and 114,117 (95% UI, 80,122–150,221) DALYs, with the Caribbean among the regions with the highest burden. From 1990 to 2021, ASRs for mortality and DALYs for both OC and UC attributable to high BMI significantly increased and are projected to continue rising over the next 15 years. The burden increased with age, peaking at 45–49 years. Regionally, burden rose in low- and middle-SDI areas, while high-SDI regions showed initial increases followed by declines.ConclusionsThe rising mortality and DALYs of OC and UC attributable to high BMI, especially in low- and middle-SDI regions and high-burden areas such as Eastern Europe and the Caribbean, highlight an urgent need for targeted prevention and weight management interventions among women of reproductive age.